How is it Done? Comparison between the Margin Calculation methodology of central counterparties and clearinghouses - Friesz, Melinda; Váradi, Kata (Public Finance Quarterly, 2021)
Clearinghouses and central counterparties have become the backbone of financial markets by stepping between trades, facilitating securities trading, and derivative transactions on exchanges and overthe-counter markets. In the literature and in practice, too, the notion of clearinghouse and central counterparty are used as synonyms, but there is still a slight difference that highlights their distinction. This paper focuses on the margin calculation methodology of these institutions and emphasizes the contrast between the two. Results show that although capturing the same risks, clearinghouses’ margin requirement is better from a procyclicality and cash flow management point of view; however, central counterparties margining is more prudent based on our results.